Comparative Analysis between Conventional Plaster Models and Digital Models in the Accuracy of Prosthetic Adaptation - Belandria, Cesar Daniel Avendaño (Revista JRG de Estudos Acadêmicos, 2025)
The comparison between conventional plaster cast models and digital models in the accuracy of prosthetic fitting is a relevant topic in modern dentistry. Several studies have shown that digital models, obtained by intraoral scanning, have advantages in terms of accuracy, processing time, and patient satisfaction over conventional plaster models. While both methods can be effective, digital models offer greater flexibility, allowing for better fitting of prostheses, with fewer impression errors and greater reproducibility. However, it is important to consider the variations that may occur depending on the scanning technique and the region of the dental arch, which can influence the final results. This study aims to analyze the benefits and limitations of each method, in order to offer a clear orientation for dental professionals in choosing the best technique for prosthetic fitting.